Analisis Peningkatan Kualitas Sistem Pengendalian Retur Pembelian di PT XXX Berbasis Coso Framework - Ingrid Susanto; Bagas Brian (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
This study aims to analyze the improvement in the quality of the purchase return information system at PT XXX by optimizing the return feature in PowerPro and to evaluate its effectiveness using the COSO Framework as a reference for internal control. Data were collected through direct observation and documentation studies during the internship in the Receiving section. An analysis was conducted by comparing field practices with accounting theory and PSAK standards, and by evaluating the features available in the PowerPro Inventory system. The results show that the current return procedure, which uses a negative purchase journal, leads to recording distortions, weak internal controls, and the absence of valid transaction records. The implementation of the return feature in PowerPro improves the recording structure by adding return debit and inventory credit journals, increases transparency, accuracy, and and accountability, and strengthens the COSO components, especially control activities, information and communication, and monitoring. The implementation of the PowerPro-based return system significantly improves information quality, improves internal controls, and ensures compliance with accounting standards